Incorporating ‘First-World mindset’ into human capital enhancement for national development in Malaysia: the role of formal education - Abdulai, Abdul-Mumin (2011)

(untitled)
Undoubtedly education plays a crucial role in national development by harnessing the human capital base required to support social and economic development agendas of nations. In assessing Malaysia’s development performance towards attaining a high-income status by 2020, the Government has reiterated in the country’s 10th development plan the need, among others, to create the requisite talent that will commensurate a high-income, knowledge-intensive and innovation-led economy. Again, the 5th of the 10 development strategies underlying the 10th national development plan seeks to nurture, attract and retain top talent for national development, particularly to propel the country into a developed country by 2020. For this reason, attempts are far advanced to sensitize Malaysians on the need to cultivate “first-world mindset’’. In other words, to heighten public consciousness about the urgent need to work towards realizing the national development vision. This paper has, therefore, explored how this kind of development socialization could be used to enhance nurturing the needed talent through formal education; even way beyond the national vision 2020. Development socialization has, therefore, been conceptualised in this study as creating consciousness and instilling in people the need to acquire skills, attitudes and values that are appropriate to, and capable of, achieving society’s development goals. The study has used a sample of 250 university students to probe the probability that students will be willing to pursue different academic programmes from those they are currently pursuing if they were nurtured instead in programmes that the Government believed would produce the human capital required to support the national development vision. The finding has revealed a variety of reasons underlying the preparedness of the majority to undergo this development socialization, whereas a few have objected with reasons.